Correlation of the Goníaco Angle and height of the Mentonian Foramen, evaluated by computed tomography images of the jaw: Forensic Dentistry (Research, Society and Development, 2022)
Knowledge of anatomy is one of the key factors in successfully comparing dental records during an investigation of an individual in forensic dentistry. To perform this type of procedure, the professional must be able to identify and differentiate anatomical structures of the maxillofacial complex. The objective of this study was to verify if there is a correlation between the gonial angle and the mental foramen, age and gender, in patients submitted to mandibular Computed Tomography exams. The methodology of this work was based on obtaining and analyzing DICOM files, so that these images were converted to a specific image treatment program ImplantViewer (Anne Solutions, São Paulo, Brazil), and evaluated using the Panoramic Window and Cross Sections. of Computed Tomography. Males had the mental foramen more distant from the alveolar crest than females. CBCT is an important tool for visualizing anatomical structures, favoring activities inherent to Forensic Dentistry. In this study, the male gender presented the mental foramen more distant from the alveolar crest than the female gender.